Regional determinants of life insurance consumption: evidence from selected Asian economies. (November 2013) - Sen, Subir; Madheswaran, S
<x xml:space="preserve">Abstract</x> The life insurance industry in developing Asian economies is under‐developed compared with global standards. The low market penetration is attributed to full or partial government ownership and entry restrictions on foreign insurers. Regulatory changes and adoption of liberal policies have aided the growth of the life insurance industry in the past decade. At the same time, economic and social factors were expected to promote insurance awareness and consumption. In this context, the paper analyses the factors explaining life insurance demand in 12 Asian economies, including economies from the South Asian Association for Regional Cooperation and Association of Southeast Asian Nations regions, as well as China. The results suggest that income, financial depth, inflation, the real interest rate, and the youth dependency ratio are significant determinants of life insurance consumption. Foreign ownership and improved regulations may foster growth. But urbanisation and the literacy rate are among the few determinants found not to have the impact observed in previous studies. The research highlights the limitations of studies using macrodata and contributes to understanding of the growing insurance industry in the region.